EMOTIONAL INTELLIGENCE AND LEADERSHIP IN MOCHTAR LUBIS’ NOVEL HARIMAU! HARIMAU! - Manurung, Ontje Helena (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2023)
A good leader should have particular qualifications to lead a team in gaining its purpose successfully. Otherwise, problems or conflicts will arise that may fail the team. The classic novel of Mochtar Lubis’ Harimau! Harimau! deserves to be explored for it depicts the depravity of a leader that leads his team to suffering and death. This study aims to elaborate the factual structure and themes of the novel Harimau! Harimau and Wak Katok’s leadership using the structural approach and Daniel Goleman’s theory on emotional intelligence. The research has two findings. First, the story presented in an organic unity shows the plausible interrelated factual structure of character, plot, and settings. Second, the quality of Wak Katok’s emotional intelligence as a leader shows that Wak Katok lacks self-awareness (self-confidence, self-acceptance, setting realistic goals), lacks self-regulation (trustworthiness and integrity), no self-motivation (optimism) and empathy, and lacks social skills (maintaining communication).